Scalable autonic processing systems. (1st January 2003) - Shaout, Adnan; Zaman, Najamuz; Eldos, Taisir
The number of automotive functions that are controlled by computers is rapidly increasing. In the past, these functions were confined to stand-alone control units, such as the engine or ABS brake controller. In modern cars, the data exchange between different controllers has grown to a level where one or several networks are necessary to meet the communication demand [1]. Currently, automotive electronics processing is distributed in variety of functions like power train, air bag, climate control, suspension, etc. The purpose of this paper is to review related work through two state-of-the-art models, and propose a scalable design using parallel processing and fault tolerance techniques (excluding the functions of power train and transmission control electronics). The integration is based on the logical bisection of vehicle in four symmetric regions, which is critical for hardware, software, fault tolerance and ease of serviceability design. The proposed design can be implemented on any vehicle without going through the iterative system and module design cycles.